Mercury and Persistent Organic Pollutant Concentrations in African Fish Eagles, Marabou Storks, and Nile Tilapia in Uganda - Hollamby, Simon; Afema-Azikuru, Josephine; Sikarskie, James G.; Kaneene, John B.; Bowerman, William W.; Fitzgerald, Scott D.; Cameron, Kenneth; Gandolf, Rae; Hui, Gretchen N.; Dranzoa, Christine; Rumbeiha, Wilson K. (Journal of Wildlife Diseases, 2004)
The purpose of this research was to evaluate persistent organic pollutant (POP) and mercury concentrations in tissues of African fish eagles (Haliaeetus vocifer) and Nile tilapia (Oreochromis niloticus) from Lake Victoria near Entebbe and Lake Mburo, Uganda. Marabou stork (Leptoptilos crumeniferus) nestlings from urban Kampala (40 km from Entebbe) also were sampled for POPs and mercury. Total mercury was measured in the breast feathers of eight nestling and 10 adult African fish eagles from Lake Mburo, 10 nestling and five adult African fish eagles from Lake Victoria near Entebbe, and 20 nestling marabou storks from Kampala from June 2002 through January 2003. Mercury concentrations in all samples were below levels associated with adverse effects in similar species. Mercury concentrations were significantly higher in eagle adults and nestlings from Entebbe than in adults and nestlings from Lake Mburo (P#0.05). No significant differences (P$0.05) were found in mercury concentrations between sexes or between the entire fish eagle population sampled at Entebbe and marabou stork nestlings sampled at nearby Kampala. Plasma samples from the same birds were analyzed for 1,1,1-trichloro-2,2-bis(4-chlorophenyl) ethane, aldrin, hexachlorocyclohexane (a-HCH), dieldrin, endrin, heptachlor and their metabolites, as well as total polychlorinated biphenyls (PCBs). Nile tilapia whole-body cross sections collected from Lake Mburo (n53) and Lake Victoria near Entebbe (n58) also were analyzed for these POPs and mercury. No samples contained POPs or PCBs at the limits of detection except for 4,49-1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene in five adult eagle plasma samples (0.002660.0015 ppm wet weight) and five Nile tilapia samples (0.00260.001 ppm wet weight) from Entebbe.
Keywords: African fish eagle; 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane; Haliaeetus vocifer; Leptoptilos crumeniferus; Marabou stork; Mercury